2009
DOI: 10.1007/s12598-009-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Facile and green route to highly luminescent ZnS-shelled CdSe nanocrystals

Abstract: Highly luminescent CdSe/ZnS nanocrystals were obtained by adapting non-TOP-based synthesis and a subsequent two-phase ZnS shelling procedure: the core CdSe nanocrystals were synthesized in sole solvent paraffin liquid with cadmium oxide, elemental selenium, and oleic acid; the deposition of the ZnS shell was conducted by using zinc stearate in toluene and sodium sulfide in deionized water. The green and low-cost route was proved to be more efficient to constrain the size of core nanocrystals while tuning the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It can be observed that the absorption spectra of doped Ag 2 S NCs are featureless with no first discrete absorption feature evident (Figure A,B). This contrasts with II‐VI NCs, which usually exhibit a discrete absorption feature . This uncommon phenomenon may be due to the special electronic properties of Ag 2 S NCs .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It can be observed that the absorption spectra of doped Ag 2 S NCs are featureless with no first discrete absorption feature evident (Figure A,B). This contrasts with II‐VI NCs, which usually exhibit a discrete absorption feature . This uncommon phenomenon may be due to the special electronic properties of Ag 2 S NCs .…”
Section: Resultsmentioning
confidence: 91%
“…This contrasts with II-VI NCs, which usually exhibit ad iscrete absorption feature. [25][26][27] This uncommon phenomenonm ay be due to the speciale lectronic properties of Ag 2 SN Cs. [28,29] Figure 2A shows the photoluminescences pectra of the synthesized Ag 2 SN Cs with different indium-dopant concentrations prepared at 60 8C.…”
Section: Resultsmentioning
confidence: 99%
“…The PLQY of QDs increased significantly, and the maximum PLQY of InP:Cu@ ZnSe x S 1– x QDs with ∼3.5 and ∼2.8 nm cores reached 56.47% and 47.72%, respectively. It was because the ZnSe x S 1– x shell could passivate the surficial defects of InP:Cu QDs . When the proportion of Se and S in the passivation shell was changed, the PL emission peak could also be shifted (as shown in Figure b,e, Figure S11, and Figure S12).…”
mentioning
confidence: 97%
“…It was because the ZnSe x S 1−x shell could passivate the surficial defects of InP:Cu QDs. 48 When the proportion of Se and S in the passivation shell was changed, the PL emission peak could also be shifted (as shown in Figure 4b,e, Figure S11, and Figure S12). 49 When the proportion of Se increased, the PL of QDs exhibited an obvious red shift.…”
mentioning
confidence: 97%